Odpowiedzi

Najlepsza Odpowiedź!
2010-02-22T22:40:58+01:00
D)
((3,2+7/8):2,5-0,62)*(-100/3)=
((32/10+7/8):2,5-0,62)*(-100/3)=
((128/40+35/40):25/10-0,62)*(-100/3)
(163/40*10/25 -0,62)*(-100/3)=
(163/100-62/100) *(-100/3)=
101/100*(-100/3)= -10100/300= -101/3= - 33/7
g)
(-1/9+1i1/6):(1/6-1i1/3)=
(-1/9+7/6):(1/6-4/3)=
(-2/18+21/18):(1/6-8/6)=
19/18 : (-7/6)= 19/18 *(-6/7)= -114/126= -38/42= -19/21

a)
-3/7-1i11/14+2i3/14=
- 3/7-25/14+31/14= -6/14 - 25/14 +31/14=0

d)
3i3/4*1i1/5+(-1,5):2,4-1/4=
15/4*6/5-1,5:2,4-1/4=
3/2*3-o,625-1/4=9/2-0,625-1/4=4,5-0,625-0,25=4,5-0,875=3,625